2016
DOI: 10.1128/jvi.00129-16
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Type I Interferon Production by Human T-Cell Leukemia Virus Type 1 Oncoprotein Tax through Inhibition of IRF3 Phosphorylation

Abstract: Infection with human T-cell leukemia virus type 1 (HTLV-1) is associated with adult T-cell leukemia (ATL) and tropical spastic paraparesis. Type I interferons (IFNs) are key effectors of the innate antiviral response, and IFN-␣ combined with the nucleoside reverse transcriptase inhibitor zidovudine is considered the standard first-line therapy for ATL. HTLV-1 oncoprotein Tax is known to suppress innate IFN production and response but the underlying mechanisms remain to be fully established. In this study, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…Moreover, similar results were obtained by coculturing JETWT35 cells with MT-2 cells ( Fig. 4C), which is another donor cell line widely used for HTLV-1 infection (38)(39)(40)(41)(42)(43). Interestingly, this inhibition of HTLV-1 transmission by PPS became inefficient when PPS was added to the coculture 12 h later ( Fig.…”
supporting
confidence: 79%
“…Moreover, similar results were obtained by coculturing JETWT35 cells with MT-2 cells ( Fig. 4C), which is another donor cell line widely used for HTLV-1 infection (38)(39)(40)(41)(42)(43). Interestingly, this inhibition of HTLV-1 transmission by PPS became inefficient when PPS was added to the coculture 12 h later ( Fig.…”
supporting
confidence: 79%
“…Western blot analysis, coimmunoprecipitation, and quantitative RT-PCR were performed as described previously (6,43,44). For Western blot analysis, cells were lysed in RIPA buffer (10 mM Tris-Cl, pH 8.0, 1 mM EDTA, 1% Triton X-100, 0.1% sodium deoxycholate, 0.1% SDS, 140 mM NaCl, and 1 mM PMSF) that was supplemented with a protease inhibitor cocktail (BioTools, Jupiter, FL, USA).…”
Section: Protein and Rna Analysismentioning
confidence: 99%
“…However, studies came to contradicting results on how that influences the production of IFNβ. While one group showed that Tax activates TBK1 and the production of IFNβ (86), another group showed that Tax suppresses the IFN production by interaction with TBK1 (87). Interestingly, when a recent study tested how the rabies virus P protein of street strains behaves compared to laboratory-adapted strains with regard to the induction of type I IFN, they found that both street strains and laboratory strains inhibit TBK1-mediated signaling, but only the P protein of street strains also interacts with and inhibits IKKε-inducible IRF3dependent IFNβ expression (88) (Figure 1).…”
Section: Activation Of Transcription Factors and Ifn Transcriptionmentioning
confidence: 99%